Cervical to Petrous Carotid Artery High-Flow Bypass for Carotid Artery Pseudoaneurysm Through Zygomatic Approach: 2-Dimensional Operative Video. Issue 4 (30th June 2021) - Almefty, Rami O; Al-Mefty, Ossama
Abstract: Pseudoaneurysms of the cervical internal carotid artery may generate grave risk from catastrophic rupture, thromboembolic stroke, or mass effect. They have many causes, including malignancy, infection, and iatrogenic and most commonly blunt or penetrating trauma. 1 These aneurysms require treatment to eliminate their risk. Treatment options include trapping, with or without revascularization, or endovascular stenting. Trapping without revascularization requires evaluation of the cerebral collateral under a physiological challenge, which is usually done with a balloon occlusion test, which is not applicable in this lesion. 2 Occluding the carotid without revascularization carries the risk of delayed ischemia and aneurysm formation. 3, 4 Carotid stenting has been applied in the treatment of these lesions 5, 6 ; however, the extent of the lesion in our patient from the carotid bifurcation to the petrous carotid makes endovascular treatment challenging. We present a patient with a delayed post-traumatic pseudoaneurysm of the carotid artery that extended from the bifurcation to the petrous carotid who was treated with trapping and high-flow saphenous vein bypass from the proximal cervical internal carotid to the petrous carotid. Adequate exposure of the petrous carotid to perform anastomosis requires a thorough knowledge of the anatomy and surgical nuances, which we demonstrate here through a zygomatic approach. 7 The patient consented to the procedure and publication of imaging. Image at 2:28 from Al-Mefty O, Operative Atlas of Meningiomas, © LWW, 1997, with permission.